2022
DOI: 10.3390/en15072489
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Gas–Liquid Interface Evolution during Liquid Displaced by Gas of Mobile Pipeline

Abstract: The mobile pipeline is the most effective and reliable means for the emergency oil transfer task, which is temporarily laid on the field. After completing the task, the oil in the pipeline should be emptied before the mobile pipeline is removed. The oil in pipeline gradually displaced by the air is a main method of pipeline evacuation, which is the only choice of jet fuel pipeline. Due to the convection between gas and oil phases, the length of the oil–gas mixing section and the evolution of the oil–gas interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To ensure the metering performance of the water meter, the automation control system sends commands to start the water pump for the water supply to exhaust the gas in the pipeline before the daily calibration of the water meter for the flow standard device. Meanwhile, vacuum operation is carried out for the tested meter [22]. For better automatic calibration of ultrasonic water meters, the piston-type flow standard device has been designed.…”
Section: Overall Device Designmentioning
confidence: 99%
“…To ensure the metering performance of the water meter, the automation control system sends commands to start the water pump for the water supply to exhaust the gas in the pipeline before the daily calibration of the water meter for the flow standard device. Meanwhile, vacuum operation is carried out for the tested meter [22]. For better automatic calibration of ultrasonic water meters, the piston-type flow standard device has been designed.…”
Section: Overall Device Designmentioning
confidence: 99%
“…In Section comparative analysis of the entire process of slug flow formation in the experimen and OLGA models will be conducted. The figures presented in this section (i.e., Figu 23-26) have been compared with Figures 9,10,13,14,17,18,21 and 22, respectively. demonstrated that the OLGA software accurately replicates the formation of slug fl that before the slug flow occurs, the pressures at P1, P2, and P3 increase and present an irregular saw-tooth wave.…”
Section: Flow Regime Analysis and Comparisonsmentioning
confidence: 99%
“…Additionally, the experimental apparatus used can impact the fluid, introducing errors in the experimental results. Given that liquid slug flow's formation, evolution, The occurrence of liquid accumulation in pipelines may generate local blockage, which elevates pressure and friction within the pipeline, ultimately leading to a more profound issue of slug flow [12][13][14]. The motion of slug flow in pipelines presents complex regimes that can engender erosion and wall damage, contributing to further corrosion and wear.…”
mentioning
confidence: 99%